Strategi Pemasaran dalam Meningkatkan Daya Saing Usaha Ayam Petelur (Studi Kasus: Peternakan Bapak Tuani Kec. Dua Koto, Pasaman) - Hafiza Hairina; Habibatur Ridhah (ARZUSIN, 2026)
Marketing strategies in laying hen businesses have been the focus of various studies, but research that specifically discusses the formulation of marketing strategies based on an analysis of internal and external conditions in small-scale businesses remains limited. This study aimed to analyze marketing strategies in improving the competitiveness of a laying hen business at Bapak Tuani Farm in Dua Koto Subdistrict, Pasaman Regency. This study used a qualitative approach with a case study design, involving key and supporting informants selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using thematic analysis and SWOT analysis through the IFAS and EFAS matrices. The results showed that the business had strengths in product quality, self-produced feed, and a strategic location, but still faced weaknesses in the form of a small business scale, dependence on a single collector, and the absence of an egg grading system. Opportunities in the form of stable market demand had also not been optimally utilized because of limited marketing strategies and increasing competition. These findings contribute to the development of marketing strategy theory and competitive advantage in the context of small-scale agribusiness, while also broadening understanding of the importance of integrating internal and external analysis in business strategy formulation. The conclusion of this study confirms that strengthening marketing strategies through distribution diversification and increasing product added value is necessary to improve the competitiveness of small-scale laying hen businesses.